"Fats, " futurity, and the contemporary young adult novel. Issue 2 (4th May 2018) - Byers, Michele
ABSTRACT: Fat characters in young adult novels were once cautionary tales. Today, fat embodied characters are not restricted to these old narratives, and alternative avenues through which to imagine futures long denied them are opened up. What possible futures are imaginable within the diegetic constraints of young adult fiction today? A reading of a small sample of recent publications shows that contemporary young adult literature creates new spaces for, and discursive formations through which, fat bodies can be known, even as it remains tethered to a present that is not fully emancipatory.